Second earners and in-work poverty in Europe - H. Xavier Jara; Daria Popova (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Dual or multiple earnership has been considered an important factor to prevent in-work poverty. The aim of this paper is to quantify the impact of second earnership on the risk of in-work poverty and the role of the tax-benefit systems in moderating this risk. Our analysis refers to 2014 and employs EU-SILC data and EUROMOD, the tax-benefit microsimulation model for EU-28. We apply a pre-post analysis in combination with microsimulation techniques to assess the role of second earners in preventing in-work poverty. This is done by simulating a counterfactual scenario where second earners become unemployed. Our results show that the effect of net replacement rates of second earners on the probability of in-work poverty is negative and statistically significant, but in relative terms it appears to be small compared to the effects of individual labour market characteristics, such as low pay and part-time employment.
Keywords: I32; I38; J6; 330; dual earnership; social policy; income distribution; poverty; Europe; second earners